Phenomena of Acculturation: Kinds of Acculturation Between Middle East And West As Seen In The Aladdin Movie (2019) By Guy Ritchie - Dhekan Afriyanto; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
The objective of this research was to analyze kinds of acculturation between Middle Eastand West cultures can be seen in the 'Aladdin' Movie (2019) by Guy Ritchie as reflected bythe main characters. This research is classified as a qualitative research type using adescriptive approach. The data from this study comes from 'Aladdin' Movie (2019) by GuyRitchie movie and dialogue. Then, in collecting data the researcher used documentation bywatching the movie and reading the script. In analyzing data, the researcher used interactivedata analysis by Miles and Huberman. To find the research's validity, triangulation data andtriangulation source were used to check validation for the data. The result of this researchhas demonstrated that there were three kinds of acculturation such as Syncretism, Addition,and Deculturation which were all depicted in the movie entitled 'Aladdin'.Keywords: Acculturation, Cultures, Descriptive Qualitative